An integrative approach to delimit species in the Eulaema cingulata and Eulaema pseudocingulata pair (Hymenoptera: Apidae) using morphometric and molecular evidence - Andrade, Tamires de Oliveira (2021)
The study of species delimitation has been a rich scientific field that makes use of different sources of data in order to identify independently evolving lineages that might be recognized as species. Males of the solitary orchid bees Eulaema cingulata (Fabricius, 1804) and Eulaema pseudocingulata Oliveira, 2006 are morphologically similar, although differ in the shape of the velvety area of the middle leg. These nominal species are relatively commonly recorded in bee diversity studies in Brazil; they have been, however, recognized by conflicting hypotheses of interspecific delimitation. Here we investigate the limits of both nominal species combining distinct methods: geometric morphometrics (GM), phylogenetics, COI-barcoding and pairwise genetic p-distance with a species delimitation method based on multispecies coalescent. We obtained data from 126 representative specimens of the entire geographical range in which the nominal species occur and assess species boundaries under the general lineage concept. We found substantial overlapping in the shape of forewings and heads of species in the GM analysis. The results of COI-barcoding analysis showed pair-wise genetic distances lower than 3% (within E. cingulata 1.3% and within E. pseudocingulata 0.7%, while between the two species 0.95%). The Bayesian phylogenetic reconstruction clustered both species in a strongly supported monophyletic group, however, these forms were not reconstructed as distinct clades. The sequencing of UCEs recovered 2.180 homologous loci that provided no sufficient variability to recognize both forms either as different species or as independent evolutionary units. Our results support the recognition of E. cingulata and E. pseudocingulata as members of the same evolutionary unit.